ROLE OF AGGRESSIVE-PROTECTIVE FACTORS IN LESIONS OF THE GASTRODUODENAL ZONE IN ADOLESCENTS - Nargiza Salimova; Muborak Salaeva; Lola Abduraximova (Central Asian Journal of Medicine, 2022)
The high frequency of pathology of the digestive system in children, adolescents and adults, the absence of a tendency to decrease it remains one of the urgent problems of internal medicine. The aim of this study was to study the role of aggressive and protective factors in the occurrence of gastric ulcer and duodenal ulcer in adolescents. The objective of the study. The study of the peculiarities of the relationship between aggressive and protective factors in the mucous membrane of the gastroduodenal zone with its various lesions in adolescents. Material and methods. Clinical studies were carried out in the City adolescent dispensary of the city of Tashkent on four groups of patients. The first group, which was the main one, consisted of 40 patients with erosive gastritis at the age from 14 to 18 years old, including 19 boys and 21 girls. The second group, also the main one, included 36 adolescents with duodenal ulcer at the age from 14 to 18 years old, including 19 boys and 17 girls. The third group, which served as a comparison group, included 24 adult patients with erosive gastritis at the age of 18 to 25 years, of which 23 were men and 23 women. The fourth group, also a comparison group, consisted of 24 adults with duodenal ulcer at the age from 18 to 25 years, including 18 men and 6 women. Conclusion. A feature of damage to the protective mucous barrier of the gastroduodenal zone in gastric ulcer in adolescents with Helicobacter pylori is a lack of fucose, the main component of insoluble glycoproteins.